Melioidosis case cluster following heavy inter-monsoonal rains in the Eastern Province of Sri Lanka - V. R. Francis; M. Ahilen; M. Murugamoorthy; K. Arulmoly; K. T. Sundaresan; W. A. S. K. Wickramarachchi; P. Mayurathan; H. Sathkumara; S. Krishnananthasivam; J. Masakorala; A. D. De Silva; E. M. Corea (Sri Lankan Journal of Infectious Diseases, 2017)
No abstract available